Healing Through Support: Beneficial and Detrimental Practices in Parental Grief—A Qualitative Study - Lucía Pelacho-Ríos; Samuel Mayoral; María José Jorques-Infante; Gloria Bernabe-Valero (Behavioral Sciences)
This qualitative study explores the experiences of 24 parents who have experienced the death of a child, focusing on identifying practices that either facilitated or hindered their grieving process. In-depth interviews revealed key supportive practices, including emotional empathy, clear communication, and the presence of healthcare professionals during critical moments. Parents highlighted the significance of support groups, such as “Renacer”, in providing emotional connection, hope, and the opportunity for personal transformation. However, negative experiences emerged related to impersonal communication, lack of empathy, and delays in bureaucratic processes, which aggravated the pain and hindered emotional adjustment over time. The findings underscore the importance of personalized, empathetic care and the need for more efficient systems in supporting grieving parents. These insights can guide professionals in improving grief care, emphasizing respect for the emotional needs of parents and the creation of safe, supportive environments.